Creative Practitioner Inquiry in the Helping Professions
XVIII, 218 p.
Keywords: This beautiful volume offers a range of research possibilities for practitioners. Bringing together the work of a community of scholars whose work blurs the edges between the arts and social sciences in the name of practice-based inquiry, Creative Practitioner Inquiry in the Helping Professions offers engaging and accessible exemplars alongside clear explanations of the theoretical understandings and backgrounds to the approaches offered. The book’s contributors are teachers, doctors, social workers, counsellors, psychotherapists, health and community workers and organisational consultants; together they passionately engage in arts-based research as an effective and accessible instrument of inquiry, knowledge dissemination and social change.